Knowledge, Attitude and Practice Regarding Biomedical Waste Management Amongst Health Care Personnel in A Medical College Hospital in Trivandrum - Rawat Ranu; Kumar Santosh; Leela Manju (Medsci Publications, 2016)
Introduction: Health-care establishments generate huge quantities of both hazardous and non-hazardous wastes. Correct knowledge, attitude and practice (KAP) for Biomedical Waste Management (BWM) by the health care personals therefore becomes imperative. This study was undertaken to assess KAP regarding Biomedical Waste and to determine the correlation between KAP and profes- sional category. Materials and Methods: A cross-sectional study was conducted amongst 320 Health care Personnels. A pre-designed and pre- tested structured questionnaire was used for data collection. A self made scoring system was devised to categorize KAP as good, av- erage and poor. Data entry and analysis was done using SPSS ver- sion 20. Results: Doctors had majority of those with good knowledge and attitude, nurses had the same in practice while cleaning staff had majority of those with poor KAP as compared to all other catego- ries. An average level of KAP was most prevalent in each category. Knowledge and Practice were found to have significant positive correlation with professional category (p-value= 0.002 and p-value <0.001) respectively but not attitude (p-value=0.110). Conclusion: Training needs to be intensified especially for clean- ing staff as majority of those possessing poor KAP levels belonged to them and also for others as majority in each professional cate- gory possessed an average KAP level.